2021
DOI: 10.3390/bioengineering8050051
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Primary Adipose Stromal Cells Induce Elastin and Collagen Deposition by Smooth Muscle Cells within 3D Fibrin Gel Culture

Abstract: Macromolecular components of the vascular extracellular matrix (ECM), particularly elastic fibers and collagen fibers, are critical for the proper physiological function of arteries. When the unique biomechanical combination of these fibers is disrupted, or in the ultimate extreme where fibers are completely lost, arterial disease can emerge. Bioengineers in the realms of vascular tissue engineering and regenerative medicine must therefore ideally consider how to create tissue engineered vascular grafts contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…In agreement, one study found that the intraperitoneal injection of AT-MSC-EVs decreases the neointimal thickness in a mouse model of vein-graft bypass, providing a proof-ofconcept that AT-MSC-EVs can be used in the treatment of neointimal hyperplasia [41]. Furthermore, the positive effect of AT-MSC-EVs on the release of extracellular matrix proteins (deposition of fibrillar collagen and elastin) by smooth muscle cells was demonstrated in vitro by using a model of 3D culture system in [42], suggesting that AT-MSC-EVs could be used for vascular grafting applications. Taken altogether, these data indicate that AT-MSC-EVs can modulate the microenvironment of smooth muscle cells (i.e., modulation of cytokine and extracellular matrix release) and, thus, indirectly impact communication between smooth muscle cells and immune cells.…”
Section: Adipose Tissue Mesenchymal Stem Cells-derived Evsmentioning
confidence: 89%
“…In agreement, one study found that the intraperitoneal injection of AT-MSC-EVs decreases the neointimal thickness in a mouse model of vein-graft bypass, providing a proof-ofconcept that AT-MSC-EVs can be used in the treatment of neointimal hyperplasia [41]. Furthermore, the positive effect of AT-MSC-EVs on the release of extracellular matrix proteins (deposition of fibrillar collagen and elastin) by smooth muscle cells was demonstrated in vitro by using a model of 3D culture system in [42], suggesting that AT-MSC-EVs could be used for vascular grafting applications. Taken altogether, these data indicate that AT-MSC-EVs can modulate the microenvironment of smooth muscle cells (i.e., modulation of cytokine and extracellular matrix release) and, thus, indirectly impact communication between smooth muscle cells and immune cells.…”
Section: Adipose Tissue Mesenchymal Stem Cells-derived Evsmentioning
confidence: 89%
“…However, neither clear description nor further validation of these entries has been reported in the literature. Nevertheless, there is emerging evidence demonstrating the downstream functional and structural changes in the ECM spurred by stem-cell-derived-EVs [ 4 , 13 , 14 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Evs and Matrix Interactionsmentioning
confidence: 99%
“…EVs isolated from liquids such as blood plasma and cell culture media are not specific to the ECM but have the capacity to mediate repair by activating signaling pathways that contribute to matrix modulation [ 41 , 42 , 43 , 44 , 45 ]. As an example, multiple studies have reported angiogenic roles pertaining to EVs [ 53 ], although the link between EV-angiogenic and matrix-modulatory roles in the context of regeneration is not clear.…”
Section: Evs and Tissue Repair Via Matrix Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells (MSCs), widely present in dWAT, exert many of their effects via paracrine signalling 7,8 . Accordingly, replacing MSCs with their secretome for several applications 9,10 including hair loss therapies 11,12 could be advantageous.…”
Section: Introductionmentioning
confidence: 99%